Peranan Teori Interdependensi pada peningkatan pengambilan keputusan pemikiran - Hadi, Cholichul (Penerbit Goodwood, 2024)
Purpose: This study aims to bridge quantum psychology with dyadic interdependence theory by modeling relational states as entangled systems. The main focus is to examine whether decision-making in interdependent relationships exhibits patterns that go beyond classical logical predictions. Research Methodology: The research adopts a mixed-method approach. First, a quantum probability framework is applied to predict non-local correlations in partner judgments, including the simultaneity of trust and conflict. Second, a behavioral experiment was conducted with 150 couples, where they faced a series of conflict and collaboration scenarios. The analysis focused on violations of classical probability in interdependent choices. Results: The findings reveal the presence of quantum interference effects (|?|² = 0.78) when couples resolved conflicts. This indicates that cognitive interdependence does not fully conform to classical probability principles but instead demonstrates superpositional dynamics of attitudes that are characteristic of quantum models. Conclusions: Relational interdependence operates through quantum cognitive mechanisms that allow couples to simultaneously express trust and conflict. This challenges traditional rational frameworks and underscores the need for new perspectives in understanding dyadic relationships. Limitations: The study is limited to heterogeneous adult couples and employs an experimental design that still requires expansion into more diverse cultural contexts and relational types. Contribution: This research proposes a quantum interdependence model that redefines relational dynamics, with practical implications for couple therapy and organizational behavior, while also extending the application of quantum psychology to the social domain.